Morfotipologi Butir Pati dari Tumbuhan Pangan Papua dan Aplikasinya untuk Arkeobotani: Morfologi butir pati dari tumbuhan pangan lokal Papua sebagai Referensi Studi Arkeobotani pada konteks Arkeologi - Adi Dian Setiawan, Adi Dian Setiawan; Fajari, Nia Marniati Etie; alifah, Alifah (BRIN, 2025)
Starch grains in archaeological sites are essential to reveal the use of plants and human subsistence. This paper aims to provide reference to starch grain from local food plants originating from Papua Island. We use two methods for extracting samples: starch grains from raw and processed plant samples. We examine the starch grains using a 400x magnification polarisation microscope and ICSN 2011 to identify them. The morphological and morphotypological characteristics of starch grain from each plant are determined by applying univariate and multivariate statistical analysis. The results showed changes in the structure of the starch grain from the processed plant samples. The starch grains from the raw plant samples had different morphological and morphotypical characteristics. Variations in the shape and morphometry of starch grains are associated with typical starch from certain plants. This study provides a practical reference for identifying starch grains from archaeological sites, such as the Atiat and Karas sites.